Polemic of Artificial Intelligence (AI) Technology on the Development of Human Resources, Especially in Legal Practitioners - Jennyola Savira; Benny Djaja; Maman Sudirman (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
This concern arises because of a new technology that has become a phenomenon known as artificial intelligence machines or Artificial Intelligence (AI) which can be used in various activities, one of which is in the field of law because it can perform artificial intelligence like humans such as thinking, learning, and also self-development. This makes the role of the legal profession in providing legal services questionable. This study aims to determine the results of analysis of Artificial Intelligence (AI) machines that can potentially or not replace the role of legal practitioners and legal responsibility in the use of AI. The writing of this article uses normative research and uses conceptual and legislative approaches. Based on the results of the analysis conducted currently there is no special regulation that expressly regulates AI according to Indonesian law, AI itself is only a machine used in facilitating the work of legal practitioners and AI responsibility is imposed on the creator or user of AI because it is not a legal subject who can carry out legal actions consciously according to applicable provisions in Indonesia